Prognostic value of decline in model for end-stage liver disease score and hepatic encephalopathy in hepatitis B-related acute-on-chronic liver failure patients treated with plasma exchange. (2nd September 2022) - Wang, Lu; Zhu, Shu; Liu, Ying; Zheng, Lihua; Xu, Wenxiong; Luo, Qiumin; Zhang, Yeqiong; Deng, Hong; Li, Xinhua; Xie, Chan; Peng, Liang
Abstract: Objective: To investigate the prognostic value of Model for End-Stage Liver Disease (MELD) score and Hepatic Encephalopathy (HE) for short-term prognosis of Hepatitis B virus-related Acute-on-Chronic Liver Failure (HBV-ACLF) patients treated with plasma exchange (PE). Methods: A total of 108 patients with HBV-ACLF treated with PE were retrospectively enrolled between January 2014 to December 2020. Based on survival at 28 days, patients were divided into survival ( N  = 87) and death groups ( N  = 21). Clinical data and laboratory indicators were analyzed. Results: Compared with the survival group, the death group was associated with higher ACLF grade and incidence of HE. The levels of total bilirubin, prothrombin time, creatinine, blood urea nitrogen, MELD score, and Chinese Group on the Study of Severe Hepatitis B-ACLF II (COSSH II) score were significantly higher in the death group than in the survival group ( p  < .05). Grade 1 ACLF and the MELD score after PE treatment at one week were independent risk factors for 28-day liver transplantation-free mortality (OR = 0.062, 95%CI: 0.005–0.768; OR = 1.328, 95%CI: 1.153–1.531). A MELD score at one week of at least 25.5 was associated with a poor short-term prognosis. Of note, HE was a strong independent risk factor for a decline in MELD score at one week. (OR = 11.815, 95%CI: 3.187–43.796, p  < 0.001). Conclusion: We found patients with HE at admission and MELD score of at least 25.5 at one week after PE treatment had a poor short-term prognosis and should prompt preparation for liver transplantation. Trial Registration: The trial is registered at ClinicalTrials.gov (CT.gov identifier: NCT04231565). Registered 13 May 2020.